Efficacy and safety of pantoprazole and itopride in patients with overlap of gastroesophageal reflux disease and dyspepsia: A prospective, open‐label, single‐arm pilot study - Sundeep Lakhtakia; Aniruddha P Singh; Neeraj Singla; Sana F Memon; Duvvur N Reddy (JGH Open, 2024)
Abstract Background and Aim Combining proton pump inhibitors (PPIs) with prokinetics can provide synergistic action in patients with gastroesophageal reflux disease (GERD) and overlapping dyspepsia, but data regarding this is lacking. Methods This single‐center, prospective study evaluated the efficacy and safety of 6‐week treatment with fixed‐drug combination (FDC) of pantoprazole (PPI) and itopride (prokinetic) in 50 patients with ≥3 month history of GERD and overlapping dyspepsia refractory to pantoprazole. Efficacy was assessed as reduction in GERD symptom assessment scale (GSAS) distress score for 15 symptoms from baseline to week 6. Adverse events (AEs) were monitored up to week 6. Results Although heartburn was the most common symptom at week 6 (26.8%), its frequency significantly decreased from baseline (84.0%; P <0.01). A similar trend was observed for other symptoms: pressure/discomfort inside chest (19.5%), belching (14.6%), regurgitation (12.2%), bloating (9.8%), flatulence (9.8%), early satiety (7.3%), acidic/sour taste in mouth (7.3%), nausea (7.3%), frequent gurgling in stomach/belly (4.9%), and pressure/lump in throat (2.4%). Mean distress scores of all symptoms markedly decreased at week 6. Three AEs (n = 2) of moderate intensity were reported. Conclusion The FDC of pantoprazole and itopride showed favorable efficacy and safety in patients with GERD and overlapping dyspepsia refractory to pantoprazole monotherapy. Nevertheless, further studies are warranted.